The use of herbal remedies in urban and rural areas of the Setúbal Peninsula (Portugal): A study among elders - Santos, S. (2008)
The Setúbal Peninsula is a highly diverse area where some large-medium and small cities are concentrated and where well preserved areas integrating a natural park or reserved and protected zones can also be found. The main goals of this study were the characterization of the herbal remedies used by different populations, namely that of urban and rural areas, to compare and understand these practices, namely how they were acquired and transmitted, and to evaluate the influence of the involving flora and plant availability on its persistence. Data were obtained through semi-structured interviews to 121 persons, mainly elders. Information concerning plant’s common name, therapeutic utility, form of acquisition, harvesting procedures, parts used, way of utilization, conservation and administration, precautions or side-effects if any, evaluation of treatments efficiency, source of knowledge and other uses of the plants were recorded. Multivariate analysis of correspondences was used to characterize plants by their uses and informants by age, sex, birth-place, residence, education level, professional activity, form of plant acquisition, usage aim and regularity, and by the plants they use. Discriminant analysis was used to assess the influence of urban and rural (mountain or coastal) residence area on plants used by the informants. 186 different medicinal uses were indicated for the 253 taxa tentatively catalogued. Although many plants had various therapeutic applications, they were frequently used in physiologically related problems. Informants living in rural areas had different characteristics of those living in urban areas, their residence areas influencing the plants used.